Carbon dioxide and water incorporation mechanisms in SrFeO3−δ phases: a computational study. Issue 43 (29th October 2020) - Ford, L. J.; Slater, P. R.; Christie, J. K.; Goddard, P.
Abstract : With a higher propensity for low temperature synthesis routes along with a move toward lower solid oxide fuel cell operating temperatures, water and carbon dioxide incorporation in strontium ferrite is of importance. Abstract : With a higher propensity for low temperature synthesis routes along with a move toward lower solid oxide fuel cell operating temperatures, water and carbon dioxide incorporation in strontium ferrite is of importance. Despite this, the mechanisms are not well understood. In this work, classical-potential-based computational techniques are used to determine the favourability of water and CO2 incorporation mechanisms in both SrFeO3− δ and SrFeO2.5 . Our studies suggest that intrinsic Frenkel and Schottky type defects are unlikely to form, but that water and carbon dioxide incorporation are favourable in both phases. Water incorporation is likely for both the cubic and brownmillerite phases, with hydroxyl ions preferring to sit on octahedral oxygen sites in both structures, causing slight tilting of the shared octahedra. Interstitial hydroxyl ions are only likely for the brownmillerite phase, where the hydroxyl ions are most stable between adjacent FeO4 tetrahedral chains. Carbon dioxide incorporation via carbonate defects is most favourable when a carbonate molecule exists on an iron site, preferring the iron site with lower oxygen coordination. This involves formation of multiple oxygen vacancies surrounding the iron site, and thus we conclude that carbonate can trap oxygen vacancies.